PEMBELAJARAN MAHARAH AL-KITABAH BERBASIS BLENDED LEARNING DI TINGKAT PERGURUAN TINGGI - Halimatus Sa'diyah (UIN Maulana Malik Ibrahim Malang, 2019)
Arabic is one of the international languages taught at the university level, especially on Islamic religious campuses. The learning is related to four skills that must be mastered, including maharah al-kitabah (writing skills). At present, the world of education is experiencing rapid development, thus demanding innovation by academics to continue to improve the quality of learning. The change also refers to the selection of the right learning strategy. The change also refers to the selection of the right learning strategy. Moreover, lecturers in the modern era are not the only source of learning. The prevalence also applies to learning Arabic for students. Technological advancements become familiar to students at the university level. Nevertheless, the existence of lecturers as facilitators remains a significant need. Therefore, Blended learning is one of the learning strategies that can be used as an alternative choice for lecturers to deliver al-kitabah (writing skills) Arabic language in accordance with the objectives to be achieved.